Community acceptance of yeast interfering RNA larvicide technology for control of Aedes mosquitoes in Trinidad - Stewart, Akilah T. M. (PLoS One, 2020)
RNA interference (RNAi), a technique used to investigate gene function in insects and other organisms, is attracting attention as a potential new technology for mosquito control. Saccharomyces cerevisiae (baker’s yeast) was recently engineered to produce interfering RNA molecules that silence genes required for mosquito survival, but which do not correspond to genes in humans or other non-target organisms. The resulting yeast pesticides, which facilitate cost-effective production and delivery of interfering RNA to mosquito larvae that eat the yeast, effectively kill mosquitoes in laboratory and semi-field trials. In preparation for field evaluation of larvicides in Trinidad, a Caribbean island with endemic diseases resulting from pathogens transmitted by Aedes mosquitoes, adult residents living in the prospective trial site communities of Curepe, St. Augustine, and Tamana were engaged. Open community forums and paper surveys were used to assess the potential acceptability, societal desirability, and sustainability of yeast interfering RNA larvicides. These assessments revealed that Trinidadians have good working knowledge of mosquitoes and mosquito-borne illnesses. A majority of the respondents practiced some method of larval mosquito control and agreed that they would use a new larvicide if it were proven to be safe and effective. During the community engagement forums, participants were educated about mosquito biology, mosquito-borne diseases, and the new yeast larvicides. When invited to provide feedback, engagement forum attendees were strongly supportive of the new technology, raised few concerns, and provided helpful advice regarding optimal larvicide formulations, insecticide application, operational approaches for using the larvicides, and pricing. The results of these studies suggest that the participants are supportive of the potential use of yeast interfering RNA larvicides in Trinidad and that the communities assessed in this investigation represent viable field sites.